The design and evaluation of a short-term group psychotherapy model for survivors of a first myocardial infarction - Frewen, Sharon H (Rhodes University, Faculty of Humanities, Department of Psychology, 2005)
There is extensive evidence that the rehabilitation of individuals with coronary heart disease needs to include psychological components to complement the exercise and dietary recommendations that are normally provided. However, psychological aspects have not been integrated into medical care in South Africa to any significant degree. Psychological interventions overseas have included the modification of the Type A behaviour pattern, stress management, cognitive restructuring, relaxation techniques, improved communication skills, the identification and expression of emotions, and emotional support. The aim of the present study was to design a short-term group intervention which incorporated these aspects and which included an exploration of the mind-body experience post infarct. In addition, the intervention aimed to increase participants' awareness of the compensatory dynamics of the Type A behaviour pattern. The intervention was tailored to South African conditions and was evaluated by means of a multiple case study design. The intervention was delivered to a group of nine coronary heart disease patients which included six survivors of myocardial infarction, the remaining participants having undergone a by-pass operation. Data included weekly feedback sheets evaluating each session, repeated measures on the Profile of Mood States, the Jenkins Activity Survey, a Spouse Rating Scale and extensive qualitative data on each participant including tape recordings of each session and data collected from a series of interviews before, during and after the programme. The feedback sheets and recordings of the sessions were used as a basis for recommendations for revising the content and structure of the programme for future use. Case narratives were written for three of the participants and provided an in-depth look at how and why individual changes did or did not occur in response to the intervention. In addition, the case narratives revealed the role played by the compensatory dynamics of the Type A behaviour pattern in complicating rehabilitation for survivors of myocardial infarction. Two participants were offered a series of individual sessions at 18-month follow-up and the material from these sessions was also used to aid in the interpretation of the data. The content of the 18-month follow-up sessions provided evidence for the importance of conducting a developmental analysis of the origins of low self-esteem and insecurity that maintain and drive the Type A behaviour pattern. In these sessions, this analysis provided the basis for a brief focused psychodynamic psychotherapy that facilitated marked changes that had not been achieved in the 12-week structured group intervention. It is recommended that future research investigate the use of brief psychodynamic psychotherapy on an individual basis as a complement to a group intervention focusing on psycho-education, building social support and management of problematic emotions in everyday situations.
Keywords: Health -- Psychological aspects; Medicine and psychology; Coronary heart disease -- Psychological aspects; Type A behavior; Stress (Psychology)